2
$\begingroup$

Can someone help me out with $$\lim\limits_{x\rightarrow 0^+}x\log(1+x^{-1})?$$ I tried Taylor's expansion to no avail.

$\endgroup$
10
  • $\begingroup$ Hint: for large $x^{-1}$ the 1 becomes negligible. Eliminating it, you return to a familiar problem... $\endgroup$
    – Ian
    Feb 18 '20 at 17:24
  • 1
    $\begingroup$ $x \rightarrow 0^+$? $\endgroup$ Feb 18 '20 at 17:25
  • 1
    $\begingroup$ @Ian, yes, you are right. Not sure how that makes the problem simpler. What is the familiar problem you are hinting at? $\endgroup$
    – mjw
    Feb 18 '20 at 17:31
  • $\begingroup$ No. $\log$ is undefined for negative values. $\endgroup$
    – Teodorism
    Feb 18 '20 at 17:54
  • $\begingroup$ @mjw I was thinking of pulling out the exponent and then taking the limit of just $x\log(x)$. Changing variables works too, of course. $\endgroup$
    – Ian
    Feb 18 '20 at 17:55
5
$\begingroup$

$$\lim_{x\downarrow 0}x\log(1+x^{-1}) = \lim_{x\rightarrow\infty} \frac{\log(1+x)}{x}=0$$

by L'Hopital's rule.

$\endgroup$
8
  • $\begingroup$ Does L'Hopital apply to limits of the form $ x\rightarrow 0^+$? (Because the limit in my question is from the right). $\endgroup$
    – Teodorism
    Feb 18 '20 at 17:39
  • $\begingroup$ left and right limits at 0 are not equal for this function. Use the right-side limit. $\endgroup$
    – Gune
    Feb 18 '20 at 17:41
  • $\begingroup$ Yes. Here is a reference: mathworld.wolfram.com/LHospitalsRule.html $\endgroup$
    – mjw
    Feb 18 '20 at 17:41
  • $\begingroup$ Is that why you changed the limit to $x\rightarrow \infty$ so that the numerator and denominator become differentiable in any open interval as $x$ goes to infinity? $\endgroup$
    – Teodorism
    Feb 18 '20 at 17:42
  • $\begingroup$ No, actually, we could have applied L'Hopital's rule to $\lim \frac{\log(1+\frac{1}{x})}{\frac{1}{x}}.$ I made the change-of-variables $w=1/x$ because the derivative is a little easier in both numerator and denominator. $\endgroup$
    – mjw
    Feb 18 '20 at 17:44
3
$\begingroup$

$$\lim_{x\rightarrow 0}x\log(1+x^{-1})=\lim_{x\rightarrow 0}x\log(x^{-1}(x+1))=\lim_{x\rightarrow 0}x\log(x+1)-\lim_{x\rightarrow 0}x\log x = 0-0=0$$

We know that $\lim_{x\rightarrow 0}x\log x=\lim_{x\rightarrow 0}\frac{\log x}{\frac{1}{x}} $ using L'Hopital's rule

$$\lim_{x\rightarrow 0}x\log x = \lim_{x\rightarrow 0}\frac{\frac{1}{x}}{-\frac{1}{x^2}}=\lim_{x\rightarrow 0}x=0$$

$\endgroup$
0
$\begingroup$

$$\lim_{x\rightarrow 0}\ln\left(1+\frac{1}{x}\right)^{x}=\lim_{x\rightarrow 0}\frac{\ln\left(1+\frac{1}{x}\right)}{\frac{1}{x}}=\frac{\frac{-\frac{1}{x^{2}}}{1+\frac{1}{x}}}{-\frac{1}{x^{2}}}=\frac{x+1}{x}=1$$

$\endgroup$
1
  • $\begingroup$ Are you sure about this? $\endgroup$
    – Gune
    Feb 18 '20 at 17:29

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.